Study of Antioxidant Activity, Total Phenolic Content (TPC), and Total Flavonoid Content (TFC) of Ethanolic Extract Mango Peel (Mangifera indica L.) - Wigati, Dyan; Pratoko, Dwi Koko (Jurnal Sains dan Kesehatan, 2024)
Mango is one of the fruits rich in phenols and flavonoids, proven to have the ability to scavenge free radicals. The level of compounds in the sample can influence antioxidant capacity, including the total phenolic and flavonoid content. Peel of mango is a non-edible waste. This study aims to determine the total phenolic and flavonoid content and antioxidant activity of mango peel variety arum Manis, extracted by percolation using 70% ethanol. The total phenolic content was measured using Folin-Ciocalteu method, and flavonoid content was measured using AlCl3. The absorbances were measured using UV-Vis spectrophotometry. The DPPH radical scavenging assay to assess antioxidant activity. The result reveals that the mango peel's ethanol extract had a total phenolic content of 19.31±0.41 mgGAE/g extract, a total flavonoid content of 22.06±1.74 mgQE/g extract, and an IC50 value of 766.444 ppm. This research showed that mango peel's antioxidant activity is weak compared to standard vitamin C (6.414 ppm). This is possibly due to the low level of metabolite content, including complexities of the phenolic and flavonoid types in the extract.